Oligopolistic competition and optimal monetary policy - Ester Faia (Kiel Institute for the World Economy (IfW), 2009)
The literature has shown that product market frictions and firms dynamic play a crucial role in reconciling standard DSGE with several stylized facts. This paper studies optimal monetary policy in a DSGE model with sticky prices and oligopolistic competition. In this model firms' monopolistic rents induce both intra-temporal and intertemporal time-varying wedges which induce inefficient fluctuations of employment and consumption. The monetary authority faces a trade-off between stabilizing inflation and reducing inefficient fluctuations, which is resolved by using consumer price inflation as a state contingent sale subsidy. An analysis of the welfare gains of alternative rules show that targeting mark-ups and asset prices might improve upon a strict inflation targeting.
Keywords: E3; E5; 330; Product market frictions; oligopolistic competition; optimal monetary policy; Geldpolitik; Dynamisches Gleichgewicht; Allgemeines Gleichgewicht; Stochastischer Prozess; Oligopol; Preisrigidität; Theorie